Estudo do aproveitamento de conchas de mariscos visando a incorporação em massa de porcelanato - Fulgêncio, Erik Benigno Grisi de Araújo (2015)
One of the most important activities undertaken by the fishing communities of municipality of Cabedelo, PB, is the fishing clams. The beneficiation process generates a great quantity of shells after the mollusk extraction, whose disposal, in considerable amount, in mangrove environment, causes silting of large areas and environmental unbalance as consequence. On the other hand, the existence of the white ceramic products industries in Paraíba suggests the checking of possibility of using these clamshells, rich in calcium carbonate, in ceramic bodies’ compositions as well as replacement of calcite used in these compositions. The possibility of using these clamshells in porcelain tiles composition has been studied in this work present definite proportions aiming the optimization of the composition. Therefore, the porcelain tile mass, calcite and clamshells powder have been characterized by X-ray diffraction, X-ray fluorescence, thermal gravimetric analysis, thermal differential analysis and particle size analysis. After masses formulations, the test ceramic bodies has been obtained by uniaxial pressing. After sintered at 1210°C, 1220°C and 1230°C, the test ceramic bodies has been evaluated by technological tests, such water absorption, apparent porosity, flexural strength and linear shrinkage of drying and firing. The tests has been performed according to the recommendations of the ABNT relevant standards for BIa ceramic coating group. The results indicated which the incorporation of clamshells powder, up to 7% by weight, retains the properties of the ceramic bodies within the standards required by ABNT (13818/1997 – Placas cerâmicas para revestimentos – Especificação e Métodos de Ensaios). It has concluded which the introduction of the clamshells will be able to aggregate economic and social benefits, contributing to the environmental impacts reduction, caused by improper disposed of clamshells from processing of the fishing clams.